2007
DOI: 10.1002/gps.1833
|View full text |Cite
|
Sign up to set email alerts
|

Associations between head circumference, leg length and dementia in a Korean population

Abstract: Smaller head size and shorter limb length were associated with lower early-life socio-economic status. Both factors were apparently independent markers of risk for dementia which may indicate risk factors occurring in childhood affecting both brain and skeletal development. Associations were principally present in women. Reasons for gender differences in associations require clarification but, for this population and age group, may include preferential treatment of male children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 32 publications
2
60
3
Order By: Relevance
“…One prospective study and two cross-sectional studies showed a stronger association between height and dementia in women than in men. 12,33,36 We found the converse. It is possible that this disagreement relates to power or to the different outcomes: the studies referred to above used a clinical diagnosis of dementia as their outcome, as opposed to dementia-related death used in our study.…”
Section: Mechanisms Of Effectmentioning
confidence: 68%
See 2 more Smart Citations
“…One prospective study and two cross-sectional studies showed a stronger association between height and dementia in women than in men. 12,33,36 We found the converse. It is possible that this disagreement relates to power or to the different outcomes: the studies referred to above used a clinical diagnosis of dementia as their outcome, as opposed to dementia-related death used in our study.…”
Section: Mechanisms Of Effectmentioning
confidence: 68%
“…A number of studies have reported a dose-response association, 11,12,35,37 but the majority have treated height as a continuous measure without demonstrating a linear relationship. 28,32,33,36,38,39 We were able to demonstrate a statistically significant, dose-response association between decreasing height and dementia death. One prospective study and two cross-sectional studies showed a stronger association between height and dementia in women than in men.…”
Section: Mechanisms Of Effectmentioning
confidence: 83%
See 1 more Smart Citation
“…Shorter leg length, arm span, and maximal adult height have already been shown to be associated with cognitive impairments in late life in several studies. [12][13][14][15][16][17] Differences in these anthropometric measures may reflect nutritional or other deficits throughout childhood. 14 Thus, these studies suggest that deprivation during the critical growing years has the potential to place an individual at greater risk for cognitive deficits in later life.…”
mentioning
confidence: 99%
“…Our result of the strong correlation between intracranial cavity and brain volume supports that of the previous study by Koh et al (2005) which reported an effect of body height on whole brain volume. Brain volume is influenced by intracranial cavity volume and head size, and head size correlates with leg length (Kim et al 2008), which is one of the important contributors of stature. Therefore, a positive correlation should be expected between body height and intracranial cavity volume, which was supported in this study.…”
Section: Discussionmentioning
confidence: 99%